O sujeito professor em artigos de opinião: um olhar dialógico - Ramos, Suzianne Cristine Cordeiro (2019)
The discourses produced by the media and society, mostly, figure a negative and undervalued image of the teacher. Thinking about it, this dissertation work is guided by the following question: What senses can be convoked in two opinion articles, signed by columnist Claudio de Moura Castro, which thematizes a subject teacher. To answer this problem-question, a research eligible as a general objective, analyzes how, dialogically, Castro puts the discussion teacher subject in Brazil. In relations to the specifics, we emphasize the following: a) identify the place of speech of the articulator from the announcements convoked in the production of the two articles in analysis and b) to understand the effects of irony present in the articles in study. Therefore, we based in the assumptions of Discursive Dialogical Analysis (DDA). It´s about, then, a study of a qualitative nature, which shows as descriptive-interpretative, whose theoretic methodological approach used was dialogic, comparing texts in the time and answers in which some give to others and presenting how the discourses has been concretized, has occupied the place of social interaction and elicit answers, once the texts cannot be analyzed without considering they are discourses-answers. The selected corpus is constituted by two opinion articles from Veja magazine, entitled “Does Professor receive badly?” And “Where teachers get wrong?”. The texts were published, respectively, in July and November of 2016 and are written by columnist Claudio de Moura Castro. We are anchored in the concepts of dialogue, verbal interaction, discursive genre and discourse from the perspective of ADD, represented by Bakhtin (2011), Bakhtin / Volochínov (2014), Brait (2012), Fiorin (2016), Volochínov (2013), Volochínov / Bakhtin (2008), among others. In the point of view of research results, we have concluded that all narrative is disseminated by the analyzed articles, provoking valuative meanings that demote the teaching profession. So, we perceive that those discourses of our corpus are full of taking of position, the tonality dialogical and the dialogical values and that reflect and refract the position of the enunciator in relation what is announced.